The Implementation of Regional Regulation in Semarang Regency Number 7 of 2016 Concerning about Population Administration Case Study Death Registration in Semarang Regency - Indra Hadistia Kurniawan; Ari Subowo (Journal of Public Policy and Management Review, 2021)
Republic of Indonesia has a national principle of Pancasila and explain to UUD 1945 has an duty to provide legal status about population event felt by citizens to be reported to government. Citizens are basic elements of the state. Without citizens it is impossible for country to run its life cycle, and population will continue to grow and experience events in their lives such as marriage, birth or death.Purpose of this study is to explaining implementation Population Administration case study death registration in Semarang Regency and to finding factors that influence policy implementation using The Theory of Van Meter and Van Horn. This study uses qualitative research method and source of data come from interview, observation and documentation. The Result of research is Disdukcapil of Semarang Regency had tried implementation this policy with some program they have, however the programs still have some obstacles. The policy is obstacled by characteristic of executor, communication between organization, characteristic of executor, and socio economic of community. And policy supported by standards and objetive of the policy, Disposition of executor. The Researcher recommendation is add more staff, improvement of facilities, improvement socialization to community